2004
DOI: 10.1152/ajpendo.00114.2004
|View full text |Cite
|
Sign up to set email alerts
|

Short-term resistance to diet-induced obesity in A/J mice is not associated with regulation of hypothalamic neuropeptides

Abstract: . Shortterm resistance to diet-induced obesity in A/J mice is not associated with regulation of hypothalamic neuropeptides. Am J Physiol Endocrinol Metab 287: E662-E670, 2004; 10.1152/ajpendo.00114.2004.-To investigate the mechanisms underlying long-term resistance of the A/J mouse strain to diet-induced obesity, we studied, over a period of 4 wk, the expression of uncoupling proteins in brown adipose tissue and the expression of hypothalamic neuropeptides known to regulate energy homeostasis and then used mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Several authors have recently shown that high fat diet do not always induce body weight gain in animals (Bullen et al, 2004;Jaberi, 2004;Kovacs et al, 2003). Possible explanations for this phenomenon could be due to diet-induced thermogenesis, which plays an important role in energy homeostasis and maintain a constant body weight range.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have recently shown that high fat diet do not always induce body weight gain in animals (Bullen et al, 2004;Jaberi, 2004;Kovacs et al, 2003). Possible explanations for this phenomenon could be due to diet-induced thermogenesis, which plays an important role in energy homeostasis and maintain a constant body weight range.…”
Section: Discussionmentioning
confidence: 99%
“…7 The arrays were hybridized for 12 hours and were washed, dried, scanned and quantitated on GenePix ® 4000B microarray scanner (Molecular Devices, Sunnyvale, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Labeled control cDNA was made from Total RNA control samples (Universal Mouse Reference RNA, catalog #740100, Stratagene) using Cy3 dCTP (Perkin-Elmer), and labeled liver cDNA was made from total RNA experimental samples using Cy5 dCTP (Perkin-Elmer) during reverse transcription, as described previously [17]. …”
Section: Methodsmentioning
confidence: 99%
“…Arrays contained 17,280 features, printed from a synthesized oligonucleotide mouse library (Operon) as described previously [17]. …”
Section: Methodsmentioning
confidence: 99%